Computer Simulation of Two Component Dense Plasma by Molecular Dynamics Method (Communications in Computational Physics, 2020)
In the present work two component dense semiclassical plasma of protonsand electrons is considered. Microscopic and electrodynamic properties of the plasmaby molecular dynamic simulation are investigated. For these purposes semiclassicalinterparticle potential which takes into account quantum mechanical diffraction andsymmetry effects is used. The considered range of density of plasma is n=1022cm−3 to n=1024cm−3. Fluctuations and dynamic dielectric functions were calculated usingvelocity autocorrelation functions.